Determinants of customer continuance intention of online shopping - Talal Al-maghrabi; Charles Dennis; Sue Vaux Halliday; Abeer BinAli (International Journal of Business Science & Applied Management (IJBSAM), 2011)
The purpose of this study is to clarify theory and identify factors that could explain the level of continuance intention of e-shopping. A revised technology acceptance model integrates expectation confirmation theory and investigates effects of age differences. An online survey of internet shoppers in Saudi Arabia. Structural equation modelling and invariance analysis confirm model fit. The findings confirm that perceived usefulness, enjoyment and social pressure are determinants of e-shopping continuance. The structural weights are mostly equivalent between young and old but the regression path from perceived usefulness to social pressure is stronger for younger respondents. This research moves beyond e-shopping intentions to factors affecting e-shopping continuance, explaining 55% of intention to continue shopping online. Online strategies cannot ignore direct and indirect effects on continuance intentions. The findings contribute to literature on internet shopping and continuance intentions in the context of Saudi Arabia.
Keywords: 650; Internet shopping; e-shopping; technology acceptance; young and old examination; continuance e-shopping; Saudi Arabia